Development of selective FGFR1 degraders using a Rapid synthesis of proteolysis targeting Chimera (Rapid-TAC) platform. (1st November 2022) - Guo, Le; Liu, Jin; Nie, Xueqing; Wang, Taobo; Ma, Zhi-xiong; Yin, Dan; Tang, Weiping
Graphical abstract: Highlights: A library of FGFR degraders were prepared using a rapid synthesis of PROTAC (Rapid-TAC) platform under miniaturized conditions. Selective EGFR1 degraders were designed, synthesized and evaluated in cell-based assays. Degrader LG1188 inhibits the proliferation of FGFR1 amplification DMS114 and NCI-H1581 cells with IC50 s of 139 and 160 nM, respectively. Abstract: Proteolysis Targeting Chimera (PROTAC) has emerged as a novel therapeutic strategy. The major bottleneck for the development of PROTACs is the need to screen multiple parameters to create an effective degrader. It often involves the synthesis of dozens to hundreds of compounds one by one through a tedious process. We have developed a two-stage approach that allows for the rapid synthesis of PROTACs (Rapid-TAC) using preassembled building blocks to screen multiple parameters simultaneously. We herein report the application of this method to the development of PROTACs for FGFR, a challenging membrane protein target. In the first stage, we prepared 24 potential PROTACs quickly from a hydrazide-containing FGFR inhibitor and our previously reported VHL and CRBN ligand library bearing various linkers and an aldehyde functional group. These 24 PROTACs were then directly used for screening in cellular assay for protein degradation. Multiple hits were identified from the initial screening. We then prepared the corresponding stable analogues by replacing the hydrolytic labile acylhydrazone motif with an amide in the second stage. Among them, PROTAC LG1188 was identified as a potent and selective FGFR1 degrader.